Metabotropic Glutamate Receptor Subtype 5 Positron-Emission-Tomography Radioligands as a Tool for Central Nervous System Drug Development: Between Progress and Setbacks - Anne-Claire Dupont; Nicolas Arlicot; Johnny Vercouillie; Sophie Serrière; Serge Maia; Frédérique Bonnet-Brilhault; Maria-Joao Sa (MDPI AG, 2023)
The metabotropic glutamate receptor subtype 5 (mGluR5) is a class C G-protein-coupled receptor (GPCR) that has been implicated in various neuronal processes and, consequently, in several neuropsychiatric or neurodevelopmental disorders. Over the past few decades, mGluR5 has become a major focus for pharmaceutical companies, as an attractive target for drug development, particularly through the therapeutic potential of its modulators. In particular, allosteric binding sites have been targeted for better specificity and efficacy. In this context, Positron Emission Tomography (PET) appears as a useful tool for making decisions along a drug candidate's development process, saving time and money. Thus, PET provides quantitative information about a potential drug candidate and its target at the molecular level. However, in this area, particular attention has to be given to the interpretation of the PET signal and its conclusions. Indeed, the complex pharmacology of both mGluR5 and radioligands, allosterism, the influence of endogenous glutamate and the choice of pharmacokinetic model are all factors that may influence the PET signal. This review focuses on mGluR5 PET radioligands used at several stages of central nervous system drug development, highlighting advances and setbacks related to the complex pharmacology of these radiotracers.